Pelaksanaan Pembiayaan Akad Jual Beli Pada PT. Bank Muamalat Cabang Binjai Kepada Nasabah - Aditya Efendi; Abdullah Sani; Rani Febriyanni (AGHNIYA : Jurnal Ekonomi Islam, 2022)
This study aims to determine the implementation of the financing of the sale and purchase agreement at PT. Bank Muamalat Binjai Branch to customers. The research method used in this study is a qualitative research method that is descriptive with an empirical approach. The results showed that the application of buying and selling contracts in the form of financing products at PT. Bank Muamalat Binjai Branch is motor financing, car purchase, electronic goods purchase, business raw material purchase, home renovation material purchase, and house purchase. The process and realization of the financing of the sale and purchase agreement at PT. Bank Muamalat Binjai Branch begins with an application, a survey of files, then continues with a survey of customer feasibility and collateral, then the stage of financing disbursement and the stage of repayment of financing according to the agreement. Distribution of financing for buying and selling contracts to PT. Bank Muamalat Binjai Branch is carried out by implementing the principle of prudence through the 5C aspects, namely Character, Capacity, Condition of Economy, Capital, Collateral, and 7P, namely Personality, Party, Purpose, Prospect, Payment, Profitability, Protection, and plus the 1S aspect, namely Sharia.